Financial Performance Analysis of IDX-MES BUMN 17 Companies Using the EVA and MVA Methods - Meri Popitasari; Nurul Hak; Rizky Hariyadi (Penerbit Goodwood, 2026)
Purpose: This study aims to evaluate the financial performance of companies listed in the IDX-MES BUMN 17 index during the 2019–2023 period using the Economic Value Added (EVA) and Market Value Added (MVA) methods. The objective is to provide a comprehensive analysis of the extent to which these companies generate economic and market value for their shareholders. Methodology/Approach: This quantitative study examines three companies from the IDX-MES BUMN 17 index, selected from a population of 16 companies listed between December 1, 2023, and May 31, 2024. Each company is observed over five consecutive years, yielding a total of 15 data points for analysis. Results/findings: The results indicate that during 2019–2023 all sampled firms showed weak financial performance based on EVA. Based on MVA, PT WEGE Tbk recorded negative values, while PT PGAS Tbk and PT ANTM Tbk achieved positive MVA. Conclusion: During 2019–2023, the sampled IDX-MES BUMN 17 firms showed negative EVA, indicating weak economic value creation, while market performance differed—PT WEGE Tbk had negative MVA, whereas PT PGAS Tbk and PT ANTM Tbk recorded positive MVA. Limitations: Although EVA and MVA offer insights into value creation, they rely on historical accounting data and assumptions, which may not fully capture market dynamics or future prospects of IDX-MES Soe 17 companies from 2019–2023. Contribution: This study analyzes the financial performance of SOEs on IDX-MES Soe 17 (2019–2023) using EVA and MVA, offering insights into shareholder value creation and capital efficiency.